Intelligent Agent Services in Electronic Libraries - Qader, Reem A.; Sahib, Naji M. (Iraqi Journal of Science, 2021)
Global services with an agent or a multi-agent system are a promising and new research area. However, several measures have been proposed to demonstrate the benefits of agent technology by supporting distributed services and applying smart agent technology in web dynamics. This paper is designed to build a Semantic Web on the World Wide Web (WWW) to enhance the productivity of managing electronic library applications, which poses a problem to researchers and students, represnted by the process of exchanging books from e-libraries, where the process is slow or the library needs large system data.